Validation of Patient Perception Instruments for Junior Doctor Performance: a Factor Analysis - Mia Kusmiati; Rafidah Bahari; Noor Aini Abdul Hamid; Ova Emilia; Suhaila Sanip (Faculty of Medicine, Universitas Islam Bandung, 2024)
Non-Indexed Publication